Can critical inquiry differ from criticism? A dialogue with current occupational science and occupational therapy schools of inquiry/Pode uma análise crítica ser diferente de uma censura? Um diálogo com campos de estudo na ciência ocupacional e na terapia - Wilson, Jessie; Magalhães, Lilian (Cadernos Brasileiros de Terapia Ocupacional, 2016)
Introduction: Critical inquiry has been adopted by various academic disciplines. However, there is a lack of consistency and transparency in the way this complex theoretical and methodological position is applied in research. For novice researchers that ambiguity can lead to blurring the conceptual distinction between critical research and the act of criticizing. Objective: The purpose of this essay is to reflect on what it means to keep a critical perspective for novice researchers. Method: The concepts are explored through a personal narrative that allows authors to examine the details of their trajectory to embrace a critical perspective, which has the power to lead to change, both personal and social. Results: We explore the methodological foundations of the critical research and observe how the emotion is taken over or suppressed in the investigation process. Conclusion: We contextualize key concepts of critical investigation, examining its recent application both in occupational science and in occupational therapy.